Determinación y caracterización de las concentraciones de material particulado sedimentable del sector de ladrilleras de la Matriz del Cantón Chambo - Paredes Vargas, Carlos Santiago (2019)
In Chambo which is a town located in Chimborazo province, one of the main sources of the local economy is the manufacture of bricks, which highlights the presence of 46 artisan-type kilns, which generate atmospheric pollutants such as particulate matter, monoxide and carbon dioxide. Actually, the increase in MP is considered one of the biggest problems of air pollution caused by natural and anthropic activities. The present investigation proposed the monitoring of sedimentary particulate material that was made through 7 passive monitoring seasons using Petri boxes for their collection, which were strategically located in the canton matrix, and volatile particulate material of 2.5 μm and 10 μm , was made with the use of the DustTrak ™ II equipment. MPS measurements were taken during the period from January 14 th to February 13 th, 2019. Within the analysis of the results, it was determined that seasons 1 (0.61 mg / cm2 / month), 2 (0.66 mg / cm2) / month), 3 (0.55 mg / cm2 / month), 5 (0.67 mg / cm2 / month), 7 (0.76 mg / cm2 / month) exceed the maximum values of OMS, as the season 4 (1.07 mg / cm2 / month) exceeds the LMP of OMS and TULSMA. In the analysis of the results obtained for MPV, it should be mentioned that they will not exceed the maximum values of the two regulations. The MPS samples were analyzed in the scanning electron microscope. Within the analysis of the chemical composition of the samples, 9 elements were found, in addition the particles have spherical, rounded and irregular shapes.